已知(1)X-Y+Z=0 (2)X+2Y-3Z=0 求X:Y:Z
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/07 11:27:16
已知(1)X-Y+Z=0(2)X+2Y-3Z=0求X:Y:Z已知(1)X-Y+Z=0(2)X+2Y-3Z=0求X:Y:Z已知(1)X-Y+Z=0(2)X+2Y-3Z=0求X:Y:Z(1)-(2):4Z
已知(1)X-Y+Z=0 (2)X+2Y-3Z=0 求X:Y:Z
已知(1)X-Y+Z=0 (2)X+2Y-3Z=0 求X:Y:Z
已知(1)X-Y+Z=0 (2)X+2Y-3Z=0 求X:Y:Z
(1)-(2):4Z-3Y=0,推出Y:Z=4:3
(1)*2+(2):3X-Z=0,推出X:Z=1:3
令Z=a,则Y=4a/3,X=a/3
于是X:Y:Z=a/3: 4a/3: a=a:4a:3a=1:4:3
已知x,y,z>0,xyz(x+y+z)=1,求证(x+y)(x+z)>=2
已知(1)X-Y+Z=0 (2)X+2Y-3Z=0 求X:Y:Z
已知xyz≥0,x+y+z=1,化简x(2y-z)/(1+x+3y)+y(2z-x) /(1+y+3z) +z(2x-y)/(1+z+3x)
已知:x^2/(z+y)+y^2/(x+z)+z^2/(x+y)=0,求x/(z+y)+y/(x+z)+z/(x+y)的值.
已知4x-3y-3z=x-3y+z=0(x、y、z不等于0)(1)求x:y:z (2)求2x+3y-4z/z的值
已知4x-3y-3z=0,x-3y-z=0求(1)x:z的值.(2)x:y:z的值.
已知{2x-y-z=0,3x-9y+z=0求1,x:y:z
已知(x+y+z)^2=x^2+y^2+z^2,证明x(y+z)+y(z+x)+z(x+y)=0
已知x-y/x+y=y+z/2(y-z)=z+x/3(z-x),求证8x+9y+5z=0THX..
已知x、y、z满足方程组:x+y-z=6;y+z-x=2;z+x-y=0 求x、y、z的值
已知X.Y.Z满足方程组,X+y-Z=6y+z-x=2z+x-y=0求X.Y.Z的值
已知x,y,z 大于0,x+y+z=2,求证 xz/y(y+z)+zy/x(x+y)+yx/z(z+x)大于等于2/3
已知实数x y z满足x/(x+1)=y/(y+2)=z/(z+3)=(x+y+z)/3,求x+y+z的值
已知实数x y z满足x/(x+1)=y/(y+2)=z/(z+3)=(x+y+z)/3,求x+y+z的值
已知xyz满足(x/y+z)+(y/z+x)+(z/x+y)=1,则代数式(x^2/y+z)+(y^2/z+x)+z^2/x+y的值为
已知y+z分之x=z+x分之y=x+y分之z(x+y+z≠0)求x-y+z分之x+2y+z的值
已知x/2=y/3=z/4,求下列各式 (1)(x+y+z)/x (2)(x-y+2x/(x-y-2z)
已知x+y-7z=0 x-2y+5z=0(xyz不等于0),求x+2y-z/y-2x+12z